2008
DOI: 10.3797/scipharm.0804-07
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Quality Control and Biodistribution Studies of two [111In]-Rituximab Immunoconjugates

Abstract: In order to use Auger-electron therapeutic effects in CD20 antigen targeting in lymphomas, Mabthera™ (rituximab) N-succinimidyl-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetra-acetic acid (DOTA-NHS) and ccDTPA separately. Conjugated-Rituximab was obtained by the addition of 1 ml of a rituximab pharmaceutical solution (5 mg/ml, in phosphate buffer, pH=7.8) to a glass tube pre-coated with freshly prepared DOTA-NHS or ccDTPA (0.01-0.1 mg) at 25°C. Radiolabeling was performed at 37°C in 3hand room temperature for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The HPGe detector gives us count; therefore, we had used the below formula to convert the counts into the activity [30]:…”
Section: Measurement Of Activitymentioning
confidence: 99%
“…The HPGe detector gives us count; therefore, we had used the below formula to convert the counts into the activity [30]:…”
Section: Measurement Of Activitymentioning
confidence: 99%
“…On the basis of the promising results of the biodistribution data of 4-benzyl-1-(3-[ 125 I]-iodobenzylsulfonyl)piperidine (4-B-[ 125 I]-IBSP) obtained from normal rats, it was concluded that this tracer may be used as an imaging agent for early detection of various cancers such as breast, prostate, liver, and lung cancers, although internal dosimetry calculations are still needed. Pursuant to our previous studies on the estimation of human absorbed doses based on biodistribution data obtained from rodents [18][19][20][21][22], in the current study, the authors endeavored to perform a robust description of organ biodistribution because of a large amount of biodistribution data (source organs in dosimetry calculations). Efforts were taken to estimate the effective radiation dose absorbed by human organs following intravascular administration of 4-B-[ 125 I]-IBSP by using biodistribution data from normal rats.…”
Section: Introductionmentioning
confidence: 99%
“…Organs (blood, heart, liver, right kidney, left kidney, muscle, trabecular bone, intestine, pancreas, lung, stomach, tail, spleen and adrenal) were removed, washed with normal saline and dried in paper toweling. Each sample was weighed and counted with an HPGe detector 3 times, together with standards prepared from a sample of the injected material [26]. In order to minimize the uncertainties' all the samples counts were higher than 10,000, which results SD of less than 1 %.…”
Section: Methodsmentioning
confidence: 99%